Mitigating COVID-19 Impact on the Portuguese Population Mental Health: The Opportunity That Lies in Digital Mental Health - Mendes-Santos, Cristina; Andersson, Gerhard; Weiderpass, Elisabete; Santana, Rui (Frontiers in Public Health, 2020)
COVID-19 mitigation measures present unprecedent challenges in mental healthcare delivery, posing high risk to the mental health of at-risk populations namely, patients diagnosed with COVID-19, front-line healthcare providers and those submitted to quarantine or isolation measures, as well as, the general population. Ensuring safe and equitable access to mental healthcare by these groups entails resorting to innovative psychosocial intervention strategies such as, Digital Mental Health. In this perspective piece, we describe the impact of COVID-19 on the Portuguese population’s mental health, present an overview on initiatives developed to address the challenges currently faced by the Portuguese mental healthcare system, and discuss how timely implementation of a comprehensive Digital Mental Health strategy, coupling research, education, implementation and quality assessment initiatives, might buffer COVID-19´s impact on the Portuguese society.